Application of Redundancy and Standby Technology for BRAS in the Metropolitan Area Network - Xianfeng Wang; Tao Liu (Dianxin kexue)
Based on analyzing the present situation of the Xuzhou metropolitan area network, the redundancy and standby technology to solve the single points of failure for BRAS was presented and a detailed scheme was designed. The information synchronization between main and standby BRAS and redirect for the flow guide based on tunnel technology were used to realize seamless switching between main and standby BRAS. Even the BRAS and its link failed, the broadband was in normal use.